Lung Cancer Prediction Using Machine Learning Classifiers - et. al., Ankush Kumar Gulia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Lung Cancer is the major cause of mortality which are cancer-related. Therefore, the diagnosis, prediction and detection of this disease has become very important. Machine Learning techniques have been in use for the medication of such conditions because of their high accuracy results. For the prognosis and analysis of lung cancer in the healthcare sector, various machine learning algorithms have been utilized such as Artificial Neural Networks (ANN), Naive Bayes, Logistic Regression and Support Vector Machines (SVM). The causes of lung cancer and machine learning algorithms’ applications are discussed in this review. The advantages and disadvantages of these algorithms are also discussed. Experimental study proved that the proposed model is a highly optimized model of existing machine learning algorithms..